Transcriptional activity of repair, apoptosis and cell cycle genes (TP53, MDM2, ATM, BAX, BCL-2, CDKN1A, OGG1, XPC, PADI4, MAPK8, NF-KB1, STAT3, GATA3) in chronically exposed persons with different intensity of apoptosis of peripheral blood lymphocytes - V. S. Nikiforov; E. A. Blinova; A. I. Kotikova; A. V. Akleyev (Вавиловский журнал генетики и селекции)
Transcriptional activity of genes involved in maintaining genetic homeostasis (genes for repair, cell cycle and apoptosis: TP53, MDM2, ATM, BAX, BCL-2, CDKN1A, OGG1, XPC, PADI4, MAPK8, NF-KB1, STAT3, GATA3) was studied in chronically exposed persons with an increased intensity of early and late stages of apoptosis and necrosis of peripheral blood lymphocytes. The object of this study was peripheral blood mononuclear cells obtained from 132 chronically exposed residents of the Techa riverside villages. The mean accumulated dose to red bone marrow was 426.4±48.2 mGy (1.3–2930.0 mGy), to thymus and peripheral immune organs, 58.9±7.9 mGy (0.1–489.0 mGy). The study was performed more than 60 years after the onset of exposure, the average age of exposed persons was 68±0.6 years (55–86 years). The study of apoptotic and necrotic death of peripheral blood lymphocytes was based on the presence of phosphatidylserine on the cell membrane surface, as well as on its permeability for DNA-intercalating dye. Evaluation of the relative content of mRNA genes for repair, cell cycle, and apoptosis was carried out using real-time PCR. An increased relative content of PADI4 gene mRNA was registered in the group of chronically exposed persons with the increased intensity of early apoptosis (p = 0.006). Modulation of the relative content of mRNA of the TP53 (p = 0.013) and BCL-2 (p = 0.021) genes was detected in the group of chronically exposed individuals with the increased intensity of the late stage of apoptosis. A statistically significant increase in the transcriptional activity of the TP53 gene was observed in the group of chronically exposed persons with the increased intensity of peripheral blood lymphocyte necrosis in the long-term period (p = 0.015). In the course of the study it was noted that exposed people with increased intensity of apoptosis, first of all, demonstrate changes in the transcriptional activity of apoptotic genes. These data are consistent with current views on the activation of programmed cell death.